Amphibians and Reptiles of the Tirimbina Biological Reserve: a baseline for conservation, research and environmental education in a lowland tropical wet forest in Costa Rica - Branko Hilje; Gerardo Chaves; Jeremy Klank; Ferdy Timmerman; Joshua Feltham; Scott Gillingwater; Teresa Piraino; Emmanuel Rojas (Check List, 2020)
The Tirimbina Biological Reserve is located in the lowlands on the Atlantic versant of Costa Rica. We provide an updated comprehensive herpetofauna species list and summarize the results of all the herpetofauna research conducted at Tirimbina over the last 10 years (2009–2019) across a variety of microhabitats. We also added historical records from occasional sightings and reports from researchers, staff, visitors, interns, fellows, and volunteers since the 1990s. We found 52 amphibian and 78 reptile species on the reserve, including a few species considered at-risk according to the IUCN Red List. We conclude that Tirimbina is a herpetofauna biodiversity hot spot in Costa Rica because it provides unique habitat characteristics for a variety of species, including habitat for both forest and forest-edge specialists.